Pengenalan Aplikasi Matematika dalam Kehidupan Sehari-hari pada Anak Panti Asuhan - Talidobel, Susilo; Assa’ady, M. Chothibul Umam; Nirwana, Baiq Nadia; Putrajip, Mohamad Yudisa; Nabila, Wanda (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2023)
This community dedication aims to introduce the application of mathematics to children in orphanages. Through this activity, children are expected to understand that mathematics is not only theoretical, but also has practical applications in everyday life. The dedication methods used involve discussion, demonstration, and interactive use of mathematical applications tailored to children's level of understanding. The evaluation was conducted to measure children's understanding and interest in mathematics after the intervention.